2021
DOI: 10.1093/eurjpc/zwab020
|View full text |Cite
|
Sign up to set email alerts
|

Multiple hormonal and metabolic deficiency syndrome predicts outcome in heart failure: the T.O.S.CA. Registry

Abstract: Aims Recent evidence supports the occurrence of multiple hormonal and metabolic deficiency syndrome (MHDS) in chronic heart failure (CHF). However, no large observational study has unequivocally demonstrated its impact on CHF progression and outcome. The T.O.S.CA. (Trattamento Ormonale nello Scompenso CArdiaco; Hormone Treatment in Heart Failure) Registry has been specifically designed to test the hypothesis that MHDS affects morbidity and mortality in CHF patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…As elsewhere described (11), T2D and IR were associated with poor outcome [HF 1.34 (1.03-1.73), p = 0•03]; however, when considered separately, T2D and not IR patients showed a signi cant association with the primary endpoint, reaching 70% of the patients with T2D and 52% in the patients without T2D (P = 0.001). Interestingly, among diabetic patients, those displaying a greater decline in CPET performance (i.e., peak VO 2 ) and right ventricular pulmonary arterial coupling (i.e., TAPSE/PASP) were burdened by a worse prognosis.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As elsewhere described (11), T2D and IR were associated with poor outcome [HF 1.34 (1.03-1.73), p = 0•03]; however, when considered separately, T2D and not IR patients showed a signi cant association with the primary endpoint, reaching 70% of the patients with T2D and 52% in the patients without T2D (P = 0.001). Interestingly, among diabetic patients, those displaying a greater decline in CPET performance (i.e., peak VO 2 ) and right ventricular pulmonary arterial coupling (i.e., TAPSE/PASP) were burdened by a worse prognosis.…”
Section: Discussionmentioning
confidence: 67%
“…However, it is unclear whether the higher mortality observed in patients with diabetes and HF is due to hyperglycaemia per se or whether the presence of IR is already capable of affecting the HF progression. In this regard, data from the TOSCA Registry (10,11) recently con rmed that the presence of insulin impairment (IR de ned by HOMA index > 2.5 or T2D) was signi cantly associated with CV hospitalization and all-cause mortality. Of note, when adjusted for confounders, T2D alone and not HOMA-IR predicted outcome whereas HOMA-IR alone.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear whether the higher mortality observed in patients with diabetes and HF is due to hyperglycaemia per se or whether the presence of IR is already capable of affecting the HF progression. In this regard, data from the TOSCA Registry [10,11] recently confirmed that the presence of insulin impairment (IR defined by HOMA index > 2.5 or T2D) was significantly associated with CV hospitalization and all-cause mortality. Of note, when adjusted for confounders, T2D alone and not HOMA-IR predicted outcome whereas HOMA-IR alone.…”
Section: Introductionmentioning
confidence: 94%
“…Study procedures have been previously published in detail [10,11]. In brief, blood samples were collected by venipuncture after overnight fast.…”
Section: Study Proceduresmentioning
confidence: 99%
“…28-3.83), p = 0.01]. The more the number of HDs, the more the cumulative risk of worse prognosis [18].…”
Section: Hormonal Disorders In Chf Patientsmentioning
confidence: 99%